Prenatal exposure to paraquat and nanoscaled TiO2 aerosols alters the gene expression of the developing brain. (January 2022) - Hamdaoui, Quentin; Zekri, Yanis; Richard, Sabine; Aubert, Denise; Guyot, Romain; Markossian, Suzy; Gauthier, Karine; Gaie-Levrel, François; Bencsik, Anna; Flamant, Frédéric
Abstract: Nanopesticides are innovative pesticides involving engineered nanomaterials in their formulation to increase the efficiency of plant protection products, while mitigating their environmental impact. Despite the predicted growth of the nanopesticide use, no data is available on their inhalation toxicity and the potential cocktail effects between their components. In particular, the neurodevelopmental toxicity caused by prenatal exposures might have long lasting consequences. In the present study, we repeatedly exposed gestating mice in a whole-body exposure chamber to three aerosols, involving the paraquat herbicide, nanoscaled titanium dioxide particles (nTiO2 ), or a mixture of both. Particle number concentrations and total mass concentrations were followed to enable a metrological follow-up of the exposure sessions. Based on the aerosols characteristics, the alveolar deposited dose in mice was then estimated. RNA-seq was used to highlight dysregulations in the striatum of pups in response to the in utero exposure. Modifications in gene expression were identified at post-natal day 14, which might reflect neurodevelopmental alterations in this key brain area. The data suggest an alteration in the mitochondrial function following paraquat exposure, which is reminiscent of the pathological process leading to Parkinson disease. Markers of different cell lineages were dysregulated, showing effects, which were not limited to dopaminergic neurons. Exposure to the nTiO2 aerosol modulated the regulation of cytokines and neurotransmitters pathways, perhaps reflecting a minor neuroinflammation. No synergy was found between paraquat and nTiO2 . Instead, the neurodevelopmental effects were surprisingly lower than the one measured for each substance separately. Graphical abstract: Image 1 Highlights: Gestating mice were exposed to aerosols containing paraquat and/or nanoscaled titanium dioxide particles. RNA-seq analysis of gene expression in the pups striatum was used to assess neurodevelopmental consequences of in utero exposure. Both treatments are associated to alterations of gene expression in the pups'developing brain. Combining paraquat and nanoscaled titanium dioxide particles does not result in a synergetic effect.